ANALISIS DAYA DUKUNG TIANG PANCANG KELOMPOK MENGGUNAKAN SOFTWARE ALLPILE DENGAN PENDEKATAN METODE REESE - Moh Rafikanaja (Jurnal Vokasi Teknik Sipil, 2024)
In conventional analysis, using empirically tested formulas ensures the accuracy of an analysis. However, this process often takes time to achieve safe and accurate results. With technological advancements, numerous software applications facilitate structural analysis in construction. This meets the demand for efficiency and precision in analysis results, one of which is Allpile Software. AllPile is a software tool used to assist in analyzing and designing various types of foundations, including pile foundations. The analysis results of pile bearing capacity using Allpile software with the Reese method approach based on Standard Penetration Test (SPT) data yielded ultimate bearing capacities of group pile foundations with 2, 4, and 6 piles, respectively, at 173.68 tons/m2, 347.36 tons/m2, and 521.05 tons/m2.